E-book publishing success : How anyone can write, compile and sell e-books on the Internet - Oghjojafor, Kingsley; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2005)
This book contains detailed and easy-to-digest information on all aspects of writing, preparing and marketing electronic books (ebooks). It covers such aspects as: How to develop ideas to write about; How to start the compilation of the ebook; How to choose the correct ebook compiling software; How to publish the ebook; How to promote and market the ebook online and offline; How to create a website and auto responders for selling the ebook; How to collect payment from the website for selling the ebook; How to set up affiliate programmes for selling the ebook.
Part 1: Writing and compiling your e-book: What are e-books? -- Choosing a subject Research the market before you start writing -- Writing your e-book -- Preparing an attractive graphic cover for the e-book -- Compiling your writing into an e-book -- E-book compilers -- Copyright protection for your e-book -- Part 2: Publishing and marketing your e-book to millions of people -- Uploading your e-book to the Internet Designing a website for your e-book -- Selling your e-book -- Free ways of promoting and marketing your e-book -- Using free articles to promote your e-book online -- Promote and market your e-book with a free demo version and e-zine -- Using affiliate programmes and pay-per-click to sell your e-book -- Use auto responders to promote your e-book -- Offline ways of promoting and marketing your e-book -- Day-to-day marketing and promotional plan for your e-book.
Elsevier
Keywords: Electronic books -- Marketing; Electronic publishing; LANGUAGE ARTS & DISCIPLINES -- Journalism; Electronic publishing; Electronic books